Glycogen Phosphorylase: A Drug Target of Amino Alcohols in Echinococcus granulosus, Predicted by a Computer-Aided Method - Liu, Congshan; Yin, Jianhai; Hu, Wei; Zhang, Haobing (Frontiers in Microbiology, 2020)
Echinococcosis is an important parasitic disease that threats human health and animal husbandry worldwide. However, clinical drugs for this disease have poor rates. Hence, novel compounds and specific drug targets are urgently needed. In this study, we identified drug targets of amino alcohols with effects on Echinococcus secies. The drug targets were predicted with the idTarget web server. Corresponding three-dimensional structures of the drug targets were built after sequence BLAST analysis and homology modeling. After further screening by molecular docking, the activities of the candidate targets were validated in vitro. We ultimately identified glycogen phosphorylase as a potential drug target for amino alcohols. There are two genes coding glycogen phosphorylase in E. granulosus (EgGp1 and EgGp2). EgGp1 was abundant in E. granulosus PSCs, while EgGp2 was abundant in the cysts. These proteins were located at suckers and somas of E. granulosus PSCs and near the rostellum of cysts developed from PSCs. The effective compounds docked into a pocket consisting of E124, K543 and K654 and affected (either inhibited or enhanced) the activity of E. granulosus glycogen phosphorylase. In this study, we designed a method to predict drug targets for echinococcosis treatment based on inverse docking. The candidate targets found by this method can contribute not only to understanding of the modes of action of amino alcohols but also to modeling-aided drug design based on targets.